2019
DOI: 10.1534/g3.119.400392
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Genome Sequence Assemblies of Gossypium raimondii and Gossypium turneri

Abstract: Cotton is an agriculturally important crop. Because of its importance, a genome sequence of a diploid cotton species (Gossypium raimondii, D-genome) was first assembled using Sanger sequencing data in 2012. Improvements to DNA sequencing technology have improved accuracy and correctness of assembled genome sequences. Here we report a new de novo genome assembly of G. raimondii and its close relative G. turneri. The two genomes were assembled to a chromosome level using PacBio long-read technology, HiC, and Bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 26 publications
1
69
0
Order By: Relevance
“…Very recently, Udall et al reported the de novo assembly of the genome of G. raimondii and its close relative Gossypium turneri using PacBio long reads, Hi-C, and Bionano optical mapping technologies, which helped to correct some minor assembly errors in previous version of the G. raimondii genome assembly [21]. Using the same strategy, another group published a draft genome of a disease-resistant species Gossypium australe with a contig N50 of 1.83 Mb [22].…”
Section: Advances In Cotton Genomicsmentioning
confidence: 99%
“…Very recently, Udall et al reported the de novo assembly of the genome of G. raimondii and its close relative Gossypium turneri using PacBio long reads, Hi-C, and Bionano optical mapping technologies, which helped to correct some minor assembly errors in previous version of the G. raimondii genome assembly [21]. Using the same strategy, another group published a draft genome of a disease-resistant species Gossypium australe with a contig N50 of 1.83 Mb [22].…”
Section: Advances In Cotton Genomicsmentioning
confidence: 99%
“…Whole-genome alignments were generated between G. longicalyx and either G. arboreum, G. raimondii, G. turneri (Udall et al 2019), G. hirsutum (A-chromosomes), and G. barbadense (A-chromosomes) using Mummer (Marçais et al 2018) and visualized using dotPlotly (https://github.com/tpoorten/dotPlotly) in R (version 3.6.0) (R Development Core Team and Others 2011). Divergence between G. longicalyx and G. arboreum or G. raimondii was calculated using orthogroups that contain a single G. longicalyx gene with a single G. arboreum and/or single G. raimondii gene.…”
Section: Comparison Between G Arboreum and G Longicalyx For Fiber Ementioning
confidence: 99%
“…In view of cotton's importance in human life, intensive efforts have been focused on uncovering the genome mysteries of cotton species. Three diploid cottons and two tetraploid cottons were sequenced, including G. arboreum (Li et al, 2014;Du et al, 2018;Huang et al, 2020), G. herbaceum (Huang et al, 2020), G. raimondii (Wang et al, 2012;Paterson et al, 2012;Udall et al, 2019), G. hirsutum (Li et al, 2015;Zhang et al, 2015;Hu et al, 2019;Wang M. et al, 2019;Chen et al, 2020;Huang et al, 2020) and G. barbadense (Yuan et al, 2015;Liu et al, 2015;Hu et al, 2019;Wang M. et al, 2019;Chen et al, 2020). Detailed genome information is shown in Tables 1 and 2.…”
Section: Cotton Genome Sequencing Effortsmentioning
confidence: 99%
“…G. arboretum (Li et al, 2014) G. arboretum (Du et al, 2018) G. arboretum (Huang et al, 2020) G. herbaceum (Huang et al, 2020) G. raimondii (Wang et al, 2012) G. raimondii (Paterson et al, 2012) G. raimondii (Udall et al, 2019) Total contigs 40,381 8,223 2,432 1,781 41,307 19,735 187 Contig N50 (kb) 72 1,100 1, G. hirsutum (TM-1,V1.1) (Zhang et al, 2015) G. hirsutum (TM-1) (Wang M. et al, 2019) G. hirsutum (TM-1,V2.1) (Hu et al, 2019) G. hirsutum (TM-1,updated V1) (Huang et al, 2020) G. hirsutum (TM-1) (Chen et al, 2020) G. barbadense (Xinhai21) (Liu et al, 2015) G. barbadense…”
Section: Speciesmentioning
confidence: 99%
See 1 more Smart Citation